Analisis Pengaruh Persepsi Tentang Kompetensi Tenaga Teknis Kefarmasian, Kepercayaan Pelanggan dan Kualitas Layanan Terhadap Loyalitas Pelanggan Apotek Tiga Dua Lima Surabaya - Raniea Hamid (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of customer perceptions of pharmacy technician competence, customer trust, and service quality on customer loyalty at Apotek Tiga Dua Lima Surabaya. A quantitative approach was applied using a survey method with questionnaires distributed to 50 respondents selected through purposive sampling. Data were analyzed using multiple linear regression with SPSS. The results show that simultaneously, pharmacy technician competence, customer trust, and service quality significantly influence customer loyalty with a contribution of 34.5%. Partially, customer trust has a positive and significant effect and is the most dominant factor influencing loyalty. Meanwhile, pharmacy technician competence and service quality have positive but not statistically significant effects. These findings indicate that enhancing customer trust is the key strategy to improve customer loyalty, supported by continuous improvement in technician competence and service quality.